The Impact of Urban Requalification on Municipal Governance: an Analysis from Mozambique - Jochua Abrão Baloi (Britain International for Academic Research (BIAR) Publisher, 2019)
The purpose of this article is to analyze the impact of urban requalification on municipal governance, taking as a starting point the Mozambican reality. The central argument is that the urban requalification had a positive impact on the municipal governance process and contributed to local development. Thus, the question that guides this article is what is the impact of urban requalification on municipal governance in Chamanculo